Evaluation of ISSA proactive leading indicators for safety, health and well-being: Application of multi-criteria decision-making methods based on hesitant fuzzy - Mina Bargar; Mehdi Jahangiri; Moslem Alimohammadlou; Sanaz Karimpour; Mojtaba Kamalinia (PLoS ONE, 2025)
Background The Vision Zero (VZ) strategy, adopted by the International Social Security Association (ISSA), is based on seven golden rules and 14 safety, health, and well-being (SHW) indicator called VZ Proactive Leading Indicators (VZPLI). Methods The study evaluates the status of SHW VZPLI in Iran’s Petrochemical Industries by IAM-VZPLI (ISSA Assessment Method for VZPLI) and proposes a new model for assessing these indicators, called EMA-VZPLI (Extended Method for Assessment of VZPLI). EMA-VZPLI uses an integrated method consisting of multi-criteria decision-making(MCDM), the best-worst method(BWM), Decision-Making Trial and Evaluation Laboratory (DEMATEL), and axiomatic design(AD) based on hesitant fuzzy(HF) sets. Results Weight of indicators and their relationships was determined using hesitant fuzzy best-worst method (HFBWM) and Interval-Valued Hesitant Fuzzy DEMATEL(IVHF-DEMATEL) method respectively. The results showed that the C2 indicator (competent leadership) was the most important, while the C10 indicator (Procurement) was the least important. Additionally, the C2 (competent leadership) and C1 (Visible leadership commitment) indicators were dependent, showing the highest degree of dependence. The indicators of the ‘well-being’ aspect in all studied petrochemical companies were worse than those of the safety’ and ‘health’ aspects. Conclusion The results showed a significant difference in ranking of petrochemical companies for VZPLIs in EMA-VZPLI compared to IAM-VZPLI. Therefore, this method could be applied in more accurate assessment of VZPLIs of VZ indicators.